2013
DOI: 10.1038/srep03400
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Female-to-Male Sex Change in Adult Zebrafish by Aromatase Inhibitor Treatment

Abstract: This study investigated whether undifferentiated germ and/or somatic stem cells remain in the differentiated ovary of a species that does not undergo sex changes under natural conditions and retain their sexual plasticity. The effect of aromatase inhibitor (AI)-treatment on sexually mature female zebrafish was examined. A 5-month AI treatment caused retraction of the ovaries after which testes-like organs appeared, and cyst structures filled with spermatozoa-like cells were observed in sections of these tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 25 publications
5
64
1
Order By: Relevance
“…In contrast, Cyp11a1, 3b-HSD, Cyp17a1 and Cyp11b2 were not observed in the testis of XY fish until 30 dah (Kobayashi et al 1996, Morrey et al 1998. In a recent study of gonadal transcriptomes from the Nile tilapia, we further confirmed that almost all steroidogenic enzyme genes, including cyp19a1a but not including cyp11b2, were up-regulated in the XX gonads at 5 dah, while these enzyme genes, including cyp11b2 but not including cyp19a1a, were detected at 30 dah and significantly up-regulated from 90 dah onwards in the XY gonads (Takatsu et al 2013). The pivotal role of estrogens in sex determination and differentiation has been demonstrated in various teleosts (Piferrer et al 1994, D'Cotta et al 2001, Kobayashi et al 2003, Vizziano et al 2008) and other non-eutherian vertebrates (Wibbels & Crews 1994, Merchant-Larios et al 1997, Hudson et al 2005.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, Cyp11a1, 3b-HSD, Cyp17a1 and Cyp11b2 were not observed in the testis of XY fish until 30 dah (Kobayashi et al 1996, Morrey et al 1998. In a recent study of gonadal transcriptomes from the Nile tilapia, we further confirmed that almost all steroidogenic enzyme genes, including cyp19a1a but not including cyp11b2, were up-regulated in the XX gonads at 5 dah, while these enzyme genes, including cyp11b2 but not including cyp19a1a, were detected at 30 dah and significantly up-regulated from 90 dah onwards in the XY gonads (Takatsu et al 2013). The pivotal role of estrogens in sex determination and differentiation has been demonstrated in various teleosts (Piferrer et al 1994, D'Cotta et al 2001, Kobayashi et al 2003, Vizziano et al 2008) and other non-eutherian vertebrates (Wibbels & Crews 1994, Merchant-Larios et al 1997, Hudson et al 2005.…”
Section: Introductionsupporting
confidence: 73%
“…However, this is opposite to the facts: i) it is easy to induce 100% female to male sex reversal but it is difficult to induce 100% male to female sex reversal and ii) secondary sex reversal of ovary into testis has been reported in medaka, zebrafish and tilapia (Poonlaphdecha et al 2013, Takatsu et al 2013, while there Figure 5 Expression profiles of methyltransferase genes in gonads. The expression levels of the maintenance methyltransferase gene dnmt1 were up-regulated significantly, while the expression levels of the de novo DNA methyltransferases genes dnmt3 and dnmt7 were down-regulated in the MTCE 2 -XX gonad but up-regulated in the MTCE 2 -XY gonad significantly compared with their respective control.…”
Section: Discussionmentioning
confidence: 84%
“…On the basis of this unit, structural differences and similarities of testes and ovaries can be simply understood. It has been recently discovered that mature adult ovaries can be transdifferentiated into functional testes in several teleosts, including medaka [Paul-Prasanth et al, 2013], tilapia [Sun et al, 2014], and zebrafish [Takatsu et al, 2013] by inhibiting estrogen production. Testicular tissues have been suggested to originate from the germinal epithelium of ovaries [Paul-Prasanth et al, 2013], supporting the notion that the testis is an expanded version of the germinal epithelium within which spermatogenesis occurs in an organized manner.…”
Section: Resultsmentioning
confidence: 99%
“…When XX medaka was exposed to high water temperature, the physiological males could be induced along with decreasing expression of cyp19a1a, whereas co-treatment with 17β-estradiol (E2) inhibited the sex reversal [116]. Besides sex hormone, aromatase inhibitors (Fadrozole and Letrozole) could reduce the enzyme activity and thereby led to masculinization, which had been used to induce female-to-male sex reversal in tilapia and medaka [117,118]. Godwin analyzed the influence of social factors on sex determination and differentiation of reef fish, and explored the advantages of this plasticity mechanism in evolution [119].…”
Section: Plasticity Of Sex Differentiation In Fishmentioning
confidence: 99%